Regulation of human B cell activation by prostaglandin E2. Suppression of the generation of immunoglobulin-secreting cells. - Jelinek, D F (1985)
The role of prostaglandin E2 (PGE2) in the generation of immunoglobulin-secreting cells (ISC) from human peripheral blood B cells was examined. Initial studies demonstrated that monocyte (M phi)-mediated suppression of the generation of ISC in Staphylococcus aureus (SA)-stimulated cultures was mitigated by indomethacin, and thus suggested that the cyclooxygenase pathway products of arachidonic acid played a role in the regulation of B cell activation. The possibility that PGE2, one of the major products of this pathway generated by M phi-affected human B cell responses, was therefore investigated. PGE2 was found to cause concentration-dependent inhibition of the generation of ISC in pokeweed mitogen- or SA-stimulated B cell cultures supported by T cells. Studies were therefore carried out to determine whether PGE2 inhibited the production of necessary T cell factors or directly altered B cell responsiveness. Initially, the effect of PGE2 on the capacity of mitogen-stimulated cells to secrete a factor that supported the differentiation of B cells into ISC was investigated. Excessive numbers of M phi or PGE2 inhibited the production of B cell differentiation factor from mitogen-stimulated T cells. The effect of PGE2 on the capacity of B cells to differentiate into ISC was more complex. PGE2 inhibited the generation of ISC when B cells were stimulated with SA and B cell differentiation factor-containing T cell supernatants. PGE2-mediated inhibition of ISC generation was observed even when addition of PGE2 was delayed until after ISC first were detected in culture. By contrast, PGE2 caused only minimal inhibition of the generation of ISC cultures stimulated by T cell supernatants alone or protein A-free SA and T cell supernatants. These results suggested that SA-responsive B cells were particularly sensitive to inhibition by PGE2. Additional experiments supported the conclusion that B cell sensitivity to inhibition by PGE2 is augmented by the immunoglobulin cross-linking effects of protein A-containing SA. Overall, the results support the conclusion that PGE2 at physiologically relevant concentrations can influence human antibody responses by means of a direct inhibitory action on the responding B cell or an indirect one on the production of necessary T cell factors.